Pengaruh Harga dan Promosi terhadap Kepuasan Pelanggan pada Klinik Kecantikan Aiskin Padang - Mutiara, Seruni; Rahmiati, Rahmiati (ARZUSIN, 2024)
Customer satisfaction is the main goal that must be realized so that customers continue to use a product or service from a brand. There are complaints from Aiskin Padang customers regarding prices and promotions, indicating that these two aspects can influence customer satisfaction. This research is a type of causal associative research using a quantitative approach. Determining the sample size for this study used the Lemeshow formula and obtained 96 respondents with the data collection technique distributed using a questionnaire via Google Form. The data analysis techniques used are the classical assumption test and multiple regression analysis with hypothesis testing carried out using the t test, f test, and determination test with the help of the Microsoft Excel and SPSS version 20 programs. The results of this research show that all hypotheses are acceptable, 1) there are positive and significant influence between price on customer satisfaction 2) there is a positive and significant influence between promotion on customer satisfaction 3) there is a positive and significant influence between price and promotion simultaneously on customer satisfaction. The proportion of price and promotion influence is 66.0%, while the remaining 34.0% is outside this research.